Compounded markups in complex market structures - Colonescu, Constantin (My University, 2022)
Using a publicly available input-output database that covers 44 countries and 56 industries, I show that most prices are, on average, two to three times higher than the natural costs of production, costs that include a normal rate of return to capital. The novelty in this research is the argument that the true markups are compounded—they incorporate the markups already existing in the intermediate goods and services (inputs) that a company purchases in a vertical chain of production. A complex market structure, one in which companies sell and purchase intermediate products from each other in both horizontal and vertical directions, is the perfect environment for inflating a price well above its natural level. This research may help understanding the true extent of market power. Market power has a substantial impact in such matters as income inequality, standard of living, and economic development.
Keywords: complex market structure; compounded markup; monopoly pricing; world input-output tables